Women's Empowerment in Nike Advertisements: A Multimodal Analysis - Diaz Adrian; Ema Faiza (Hasanuddin University, 2022)
Aside from promoting certain products, advertisements are also utilized to promote social issues. One of the social issues promoted is women’s empowerment. This type of advertisement, which promotes women’s empowerment, is named as femvertising. In promoting this issue in a video advertisement, the combination of verbal modes and non-verbal modes are used to convey the message. The study examines two recent advertisements by Nike to reveal the message of women’s empowerment. The study used multimodal discourse analysis to examine the advertisements which were in the form of moving images, as it tried to uncover the modes present in both advertisements, and how those modes construct the discourse of women’s empowerment delivered by the narrators of both advertisements. In exploring the visual modes, Kress and van Leeuwen’s framework of visual grammar, which included representational meaning, interactive meaning, and compositional meaning, was used. The verbal analysis was explored using Hallidayan three layers of metafunction, which included the analysis of transitivity, mood structure, and theme-rheme. The study revealed that the interplay of all the modes that were analyzed put women to be doing sporting activities in sports-related settings, to possess more power than the viewers, as the most salient elements, and to be narrated with encouraging utterances in both advertisements.